THE FLEXIBLE UPPER FLOOR MADE OF LIGHT METAL STRUCTURES USING STRUCTURAL SYSTEMS - E. V. Nazarova; R. A. Khazhnagoeva; N. Y. Avetyan; A. S. Marutyan (Современная наука и инновации, 2023)
A method of increasing seismic resistance using flexible upper floors of newly erected buildings and structures, as well as reconstructed and repaired objects of existing development is presented. The technical solution of light metal structures of the complete delivery of the Novokislovodsk system is given. If in the joints of similar structures of the MERO, MARKHI, Kislovodsk system, each nodal element allows screwing up to 8 ...10 or more end bolts of rods, then one bolt is used to connect the same number of rods of the new system.